Implementing successful G2B initiatives in the HKSAR: An empirical evaluation of G2B websites. Issue 3 (2014) - ,
Abstract : Purpose – The aim of this study is to study the implementation of G2B initiatives for small‐ and medium‐sized enterprises (SMEs) in Hong Kong, focusing on the underlying importance, benefits and challenges.Design/methodology/approach – The context of this study was initially established based on comparisons with B2B initiatives. However, it is also learned from the literature that the transformational aspect of e‐Government development has not been materialized, whereas the extended web assessment method (EWAM), the three‐ring model and DeLone and McLean's IS success model were therefore identified to derive and build the theoretical G2B success model, thereby developing the online survey instrument of this study. Specifically, a positivist paradigm was adopted to investigate the impact of each G2B success factor on the overall satisfaction with using the G2B systems under examination from the perspective of SMEs, rather than simply placing emphasis on the number of electronic services provided and the investments spent.Findings – The research findings were compiled based on both the multiple regression analysis and EWAM analysis results, thus making the necessary improvements in the appropriate service aspects of the G2B systems concerned.Originality/value – The main study concluded that prevalent G2B initiatives in Hong Kong have been largely connected to pursuing conservative paradigms in public service provision. The new e‐Government strategic agenda is therefore laid out for increasing the overall transparency of new public management based on the provision of resilient‐based public services, thereby advancing the democratic empowerment of all the G2B stakeholders involved and also maximizing the multifold effects of value creations.